2019
DOI: 10.7196/samj.2019.v109i8b.13825
|View full text |Cite
|
Sign up to set email alerts
|

Human leukocyte antigen (HLA) diversity and clinical applications in South Africa

Abstract: This open-access article is distributed under Creative Commons licence CC-BY-NC 4.0.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 50 publications
0
14
0
Order By: Relevance
“…HLA class I allotypes play an important role in the control of HIV-1 viraemia [29]. Several HLA class I alleles that encode allotypes predicted to present epitopes identi ed in this study are known to be present in the South African population, including HLA-B*58:01 and HLA-A*02 that present SAAVKAACW (IN 123-131) and MASDFNLPPIV ( [22][23][24][25][26][27][28][29][30][31], respectively [28,30,49]. Past gene association studies showed that alleles within the HLA-B group correlate with greater viral control than alleles in the HLA-A and HLA-C groups [28][29]50].…”
Section: Discussionmentioning
confidence: 99%
“…HLA class I allotypes play an important role in the control of HIV-1 viraemia [29]. Several HLA class I alleles that encode allotypes predicted to present epitopes identi ed in this study are known to be present in the South African population, including HLA-B*58:01 and HLA-A*02 that present SAAVKAACW (IN 123-131) and MASDFNLPPIV ( [22][23][24][25][26][27][28][29][30][31], respectively [28,30,49]. Past gene association studies showed that alleles within the HLA-B group correlate with greater viral control than alleles in the HLA-A and HLA-C groups [28][29]50].…”
Section: Discussionmentioning
confidence: 99%
“…Alleles underlined are those that were reported to be protective [11,[28][29]49,50]. PR = protease; RT = reverse transcriptase; IN = integrase; HLA = human leukocyte antigen…”
Section: Pol Ctl Epitopes Based On Analysis Of Minority Variantsmentioning
confidence: 99%
“…This diversity presents a crucial consideration that influences the outcome of solid organ and hematopoietic stem cell transplant 2 . The recent adoption of next‐generation sequencing‐based HLA typing methodologies for the identification of compatible organ donor‐recipient pairs has aided the identification of novel HLA allelic variants 3,4 . This is especially true in African populations where the HLA allelic diversity remains relatively undefined when compared to European and North American populations 3,4 …”
Section: Figurementioning
confidence: 99%
“…2 The recent adoption of next-generation sequencing-based HLA typing methodologies for the identification of compatible organ donor-recipient pairs has aided the identification of novel HLA allelic variants. 3,4 This is especially true in African populations where the HLA allelic diversity remains relatively undefined when compared to European and North American populations. 3,4 Here we describe the detection of a novel HLA-DQB1 allele in a South African cardiac transplant candidate.…”
mentioning
confidence: 99%
See 1 more Smart Citation